Co-designing a research agenda for UK agroforestry using a multi-actor approach - Hood, Amelia S. C.; Scholes, Rosy E.; Degani, Erika; Staton, Tom; Varah, Alexa; Beauchamp, Kate; Broome, Alice; Burgess, Paul J.; Chesshire, Helen; Colbert, Edward P.; Loder-Symonds, Emma; Ramskir-Gardiner, James; et al. (Springer, 2026)
There is growing recognition of agroforestry’s potential to help mitigate and provide resilience to the climate and biodiversity crises. Beyond its environmental benefits, agroforestry can also enhance production and profits, making it a sustainable farming solution that is scalable. Despite this, uptake within Europe is low, and many knowledge gaps remain that need to be addressed to promote adoption and optimize the management and implementation of agroforestry systems. We co-developed a research agenda for agroforestry using a multi-actor approach and a modified Delphi method in 2023. 156 UK-based stakeholders contributed to this process, including farmers, advisors, policy makers, NGOs, and researchers. An initial list of 238 research priorities (high-priority research questions) was submitted via a survey and a workshop. This was shortened during a second workshop with 48 participants. The final list included 40 research priorities across the themes “environment and production,” “human livelihoods, knowledge, and perceptions,” and “policy, financing, and markets.” There was high agreement about which priorities to include, with questions on policy incentives, knowledge-exchange, agroforestry design (e.g., tree/crop selection), biodiversity, ecosystem functioning, well-being, markets, and food security. We identified a need for landscape-scale and longer-term research. Our agenda is a rare example of a research-prioritization process that includes farmers and other agricultural stakeholders throughout the research process. The value of this approach can be seen in the inclusion of research priorities that are grounded in the real world and relevant to different actors. Our agenda goes beyond existing evidence syntheses in scope, and should be used alongside them to identify stakeholder-relevant gaps for future primary research and evidence synthesis. By guiding researchers and funding bodies to impactful areas of enquiry, it can promote evidence-based agroforestry practice and policy. Addressing this research agenda requires better support for long-term, transdisciplinary, multi-stakeholder research, and funded demonstration sites or living labs.
Keywords: 4104 Environmental Management; 15 Life on Land; 2 Zero Hunger; Agronomy & Agriculture; 30 Agricultural, veterinary and food sciences; 41 Environmental sciences; 44 Human society; Agrisilviculture; Agroecology; Agroforestry knowledge-gaps; Alley cropping; Multi-stakeholder co-production; Regenerative agriculture; Research agenda; Research prioritization; Silvoarable; Silvopasture